let the first odd number = x
the sum of three consecutive odd numbers is 69
(x) + (x + 2) + (x + 4) = 69
Simplify. Combine like terms
3x + 6 = 69
Isolate the x. Note the equal sign. What you do to one side, you do to the other. Do the opposite of PEMDAS. First, subtract 6 from both sides
3x + 6 (-6) = 69 (-6)
3x = 63
Next, divide 3 from both sides to isolate the x.
3x/3 = 63/3
x = 63/3
x = 21
To solve for the third number, plug in 21 back into x.
(x + 4)
21 + 4 = 25
The third number is 25
hope this helps